THE CHALLENGE TOWARDS THE HEGEMONY OF HETERONORMATIVITY AS DEPICTED IN JENNY’S WEDDING: A PIERRE BOURDIEU’S SOCIAL REPRODUCTION THEORY - Lisa Okta Wulandari; Dewi Haryani Susilastuti (Rubikon : Journal of Transnational American Studies, 2019)
In America, the definition of marriage has changed. The Supreme Court has legalized same-sex marriage. As the growth of LGBT people slowly continues, and they keep struggle and fight for their equality, heterosexuals might feel threatened. This study aims to know how the same-sex relationship challenges the hegemony of heteronormativity and whether or not the gender norm has been shifted as proof. This study uses Jenny's Wedding (2015). It focuses on gender position, role, and responsibility in heteronormativity and homosexuality. This study uses the sociological approach and gender theory, to see the relation between heteronormativity and the individuals also Pierre Bourdieu’s social reproduction theory to see the shifting of gender norm. The finding shows that heteronormativity is used as the standard to judge, stereotype, expect things, and make assumptions. The recognition and support from society towards LGBT people and their coming out give challenges for the existenceof heterosexuals. Therefore, the contact of heteronormativity and homosexuality makes the heteronormativity no longer pure. When homosexuality affects gender norm, there must be changes in the gender norm itself.Keywords: gender; hegemony; heteronormativity; homosexuality; same-sex relationship